Navigating the nano-world future: Harnessing cellulose nanocrystals from green sources for sustainable innovation - Felix Sahayaraj Arockiasamy; Bharathi Manoharan; Vivek Mariappan Santhi; K. Prakalathan; Diwahar Periasamy; Aravind Dhandapani; Varagunapandiyan Natarajan; Senthilkumar Krishnasamy; Senthil Muthu Kumar Thiagamani; R.A. Ilyas (Heliyon)
Cellulose nanocrystals (CNCs) are a class of materials that have received significant attention in recent years due to their unique properties and potential applications. CNCs are extracted from plant fibers and possess high strength, stiffness, and biocompatibility, making them attractive materials for use in various fields such as biomedical engineering, renewable energy, and nanotechnology. This provides an in-depth discussion of the extraction, characterization, and promising applications of CNCs. Furthermore, it discusses the sources of CNCs and the methods used for their extraction as well as the common techniques used to characterize their properties. This work also highlights various applications of CNCs and their advantages over other materials. The challenges associated with the use of CNCs and the current research efforts to address these challenges were analyzed. In addition, the potential future directions and applications for CNCs were discussed. This review article aims to provide a comprehensive understanding of CNCs and their potential as versatile and sustainable materials.